ANALISA HASIL PENGELASAN PADA POSISI 1G BAJA ST37 DENGAN METODE FAULT TREE ANALYSIS - Iman Pradana A Assagaf; Ariyanto; Nurhidayat; Rizki Ilmal Yaqin; Angger Bagus Prasetiyo (Steam Engineering, 2023)
Welding is an important process in the manufacturing, metal and machinery industries, the welding results of students in the 1G Steel ST7 position are studied with the aim of identifying potential weld defects, determining root causes, evaluating and developing repair strategies to improve overall welding quality. The methods used in this research are qualitative and quantitative methods. Measuring welding dimensions with visual weld inspection, as well as liquid penetrant testing to identify weld defects. The data is processed using a Pareto diagram to determine the dominant types of defects that occur in the welding process. Once the dominant defect type is known, analysis is then carried out using the Fault Tree Analysis method. The results of the liquid penetrant test show that there are 8 types of weld defects with a total of 62 defects. In the FTA, basic events have been identified that contribute to the occurrence of weld defects, namely factors such as welding speed instability, incorrect current settings, and moist electrode. Regular evaluation, continuous monitoring and supervision during the welding process to reduce the risk of defects and improve welding quality